CHEMICAL EXAMINATION AND IN VITRO ANTIFUGAL CHRACTERIZATION OF ESSENTIAL OIL FROM AERIAL PARTS OF SWERTIA PETIOLATA D. DON - KUMAR, SANJAY; KUMAR, PAWAN; JAVED, MOHAMMAD SUHEL; GUPTA, SACHIN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of this research work was to evaluate the important phytochemical and their antifungal activity against crops pathogens from essential of Swertia petiolata. Methods: The phytochemical composition and antifungal activity of essential oil from aerial parts of Swertia petiolata D. Don obtained from hydro-distillation and analyzed by GC/GC-MS analysis in relation with their Kavot indices and mass spectra and their antifungal activity by disk diffusion method. Results: The oil is rich in monoterpenoids and oxygenated sesquiterpenoids. A total of 39 chemical constituents were identified representing 87.50% and major chemical constituents were identified as n-tetradecanal (15.16%), isopropylcyclohexene (13.58%), trimethylsilylpalmitate (12.50%), longipianol (7.76%), n-eocosane (7.46%), z-patchenal (4.40%), guaiadienal (4.07%), and heptadecanal (3.86%) whereas oxygenated monoterpenoids were minor constituents. The antifungal activity was studied by disk diffusion method with 57.63±0.10% and 44.34±0.13% mycelial growth inhibition. The oil was active against Bipolaris maydis and Rhizoctonia solani at concentration of 2.5μg/μL while, Fusarium oxysporum and Alternaria alternata were least active for this oil. The minimum inhibitory concentration and IC50 showed a range from 1.2 μg/μL to 1.8 μg/μL as compared with standard fungicides (Amphotericin and Clotrimazole) with IC50 values ranging from 0.5 μg/μL to 0.9 μg/μL and 0.5 μg/μL to 1.5 μg/μL. Conclusions: The essential oil dominated by n-tetradecanal (15.16%), isopropylcyclohexene (13.58%), trimethylsilylpalmitate (12.50%), longipianol (7.76%), n-eocosane (7.46%), z-patchenal (4.40%), and guaiadienal (4.07%) as the major components from aerial parts which showed a marked antifungal activity against Bipolaris maydis and Rhizoctonia solani.